Analisis Nilai-nilai Kementerian Keuangan Berdasarkan Perspektif Agama-agama Dharmik - Adhitama, Satria (Kamaya: Jurnal Ilmu Agama, 2024)
The Ministry of Finance of the Republic of Indonesia is a ministry that carries out an important function, namely managing state finances. There are five Ministry of Finance values ​​that must be adhered to by all employees in their attitudes and behavior, namely integrity, professionalism, synergy, service, and perfection. It is necessary to strengthen the values ​​of the Ministry of Finance among employees and officials of the Ministry of Finance so that every employee and official can apply the values ​​of the Ministry of Finance, one of which is through understanding the values ​​of the Ministry of Finance based on a religious perspective. This research aims to analyze the values ​​of the Ministry of Finance based on the perspective of religions, especially Dharmic religions, namely Hinduism, Buddhism and Confucianism. The approach used in this research is a qualitative and descriptive approach. The data collection method uses in-depth interviews and literature study. The results of this research show that the values ​​of the Ministry of Finance are contained in Hinduism which is spread in the Vedas and the Bhagavad-Gita. Buddhism also teaches a lot regarding the values ​​of the Ministry of Finance which are spread in various Suttas. Likewise with Confucianism, the values ​​of the Ministry of Finance are spread in various books in the Confucian religion.